please help show how this is done.

(4r^3+3r^4) - (r^4-5r^3)

(4r^3+3r^4) - (r^4-5r^3) = 4r^3 + 3r^4 - r^4 + 5r^3

= 3r^4 - r^4 + 4r^3 + 5r^3

= 2^4 + 9r^3 answer

what is the answer

Sorry

= 2r4 + 9r^3

2^4+9r^3 is the answer 26r

= 2r^4 + 9r^3

= r^3(2r + 9)

can this be reduced anymore, im trying to figure it out for my school student whom cannot even begin to understand.

how about a simple step by step example on how to solve it can you give me that.

Both answers are correct.

You can use = 2r^4 + 9r^3

or

= r^3(2r + 9) You can take r^3 as common.

lets get this strait,

I was taught simple do whats in brackets first.

example 4r^3 +3r^4 =1278r+27r=1305r-

125r=1180r

If you see your question, power are given on r(alphabet) not on figure.

not to solve but show equation

need to know rules of how to answer this

( 3a^2+1) - (4+2a^2)

1-4 +3a^2+2a^2

1-4+5a^2 is this the answer?

3a^2 + 1 - 4 - 2a^2

3a^2 - 2a^2 + 1 - 4

a^2 - 3 Answer (Your given answer is wrong)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up